Robust Computationally Efficient Control of Cooperative Closed-Chain Manipulators With Uncertain Dynamics - Gueaieb, Wail; Al-Sharhan, Salah; Bolic, Miodrag (Université d'Ottawa | University of Ottawa, 2007)
This article presents a decentralized control scheme for the complex problem of simultaneous position and internal force control in cooperative multiple manipulator systems. The proposed controller is composed of a sliding mode control term and a force robustifying term to simultaneously control the payload's position/orientation as well as the internal forces induced in the system. This is accomplished independently of the manipulators dynamics. Unlike most controllers that do not require prior knowledge of the manipulators dynamics, the suggested controller does not use fuzzy logic inferencing and is computationally inexpensive. Using a Lyapunov stability approach, the controller is proven to be robust in the face of varying system's dynamics. The payload's position/orientation and the internal force errors are also shown to asymptotically converge to zero under such conditions.
Keywords: Coordinated robots; Uncertain systems; Hybrid position and force control; Sliding mode control; Robust control